Me llamo Yoon - Recorvits, Helen; Swiatkowska, Gabriela (Barcelona : Juventud, 2003)
Disliking her name as written in English, Korean-born Yoon, or "shining wisdom," refers to herself as "cat," "bird," and "cupcake," as a way to feel more comfortable in her new school and new country.
Keywords: Korean Americans -- Juvenile fiction; Immigrants -- United States -- Juvenile fiction; First day of school -- Juvenile fiction; Names, Personal -- Juvenile fiction; Korean Americans -- Fiction; Immigrants -- United States -- Fiction; First day of school -- Fiction; Names, Personal -- Fiction; Spanish language materials; Coreano-americanos -- Ficcion juvenil; Inmigrantes -- Estados Unidos -- Ficcion juvenil; Escuelas -- Novela infantil; Nombres personales -- Ficcion juvenil